Karakteristik Fisiologis Enzim Nitril Hidratase dan Amidase dalam Sel Corynebacteriurn sp. D5 - Sulistinah, Nunik; Kaban, Joseva Sudiati; Sunarko, Bambang (JURNAL BIOLOGI INDONESIA, 2002)
ABSTRACTPhysiological Characteristics of Nitrile-Hydratase and Amidase From Corynebacteriumsp. D5. Nitrile hydratase (NH-ase) of Corynebacterium sp. D5 is inductive enzyme, butamidase is constitutive enzyme.The best inducer for Nitril hydratase is 2% (vlv) acetonitrille.Nitril hydratase and amidase enzymes showed to be capable of degrading low moleculeweight of aliphatic nitriles and amides. The optimum condition of NH-ase ofCorynebacteriurn sp. D5 were found out at pH 6,6 and 30Â°C while amidase at pH 7,2 & 50 Crespectively. The inhibitor of both enzymes seemed to be ~ gand H~*Key words : Nitrile hydratase, bioconversion, Corynebacterium sp. D5, amidase, acetonitrile,aliphatic nitrile